MODIFIKASI PERMAINAN TRADISIONAL DALAM PENINGKATAN MOTORIK KASAR ANAK USIA DINI DENGAN PEMBELAJARAN DI RUMAH : Penelitian Tindakan pada anak TK A Usia 4-5 Tahun TK Qurotal Aini Rancaekek Wetan Kecamatan Rancaekek Kabupaten Bandung - Puji Purwanti, - (2020)
This research is motivated by the problems that have been observed related to children's gross motor skills that aren't optimal. The purpose of this study is to improve gross motor skills in early childhood through the modification of traditional games in TK Qurotal Aini Rancaekek Wetan District Rancaekek District of Bandung. The traditional games that is played called engklek, galah jidar and boi-boian. This research is using an action research method with the subject is early childhood in the age range of 4-5 years as many as 5 children. Data collection techniques using observation techniques with two guidelines, called the scale ef asessment and field notes. Using interviews and documentation to complete the tecniques data collection. The analysis technique used is qualitative data analysis interactive models and triangulation. The results showed that the modification of traditional games can improve children's gross motor skills, in standing skills with one foot, jumping on one foot, running, catching a ball, throwing a ball and rolling a ball. Thus it can be concluded that the modification of traditional games can improve early childhood gross motor skills.